Unionization of Agricultural Workers in British Columbia - Jensen, Heather (University of Victoria, 2013)
This thesis provides a multi-method – historical, quantitative, qualitative, and jurisprudential – socio-legal case study of the unionization of agricultural workers in British Columbia. Agricultural employees have access to the Labour Relations Code of British Columbia. A historical examination of exclusion of agricultural workers from labour relations legislation from 1937 to 1975 explores the rationale behind labour relations laws and the political context of the legislative exclusion. Next, economic aspects of BC’s agricultural sector are described, with a focus on employment characteristics and the regionalised nature of agricultural production. Finally, this thesis explains the legal aspects of an ongoing campaign by the United Food and Commercial Workers (UFCW) to unionize migrant and resident agricultural workers. The union organizing campaign shows how legal labour relations processes operate in relation to migrant workers in a sector with low rates of unionization and high rates of precarious and low-paid, dangerous work.